Pemanfaatan Jenis Inokulan dengan Lama Inokulasi pada Fermentasi Limbah Sludge Kelapa Sawit untuk Pakan Ternak - John Bimasri; Fadillah Permana; Etty Safriyani (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2024)
Sludge is solid waste resulting from palm oil processing that has not been widely utilized and causes environmental pollution. The research was carried out for 2 months from March to April 2024, in Inderalaya, Ogan Ilir Regency, South Sumatra Province. The research uses experimental methods with a Completely Randomized Design (CRD). Treatment in the form of inoculam type (J), consisting of Aspergillus oryzale (J1), Rhizopus orizae (J2), and Neurospora shitophilla (J3), and fermentation time (I), consisting of 3 days (I1), 6 days (I2), and 9 days (I3). The parameters observed were dry matter, crude protein, crude fat, and crude fiber, before fermentation and after fermentation. Data were analyzed using analysis of variansces (ANOVA). Accuracy is tested with the Diversity Coefficient, and treatments that have a real to very real effect is tested using the Honestly Significant Difference Test (HST). The resulting conclusion is that sludge can be used as additional feed for ruminants, by first fermenting it using an inoculant. Sludge fermentation using the inoculant Neurosprora shitophilla produces the best quality sludge for use as animal feed, because it contains high protein and crude fat and low dry matter and fiber. The best fermentation time is 9 days, because it can reduce dry matter and crude fiber, and increase protein and crude fat.